2013
DOI: 10.1002/anie.201303449
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of McbB, an Enzyme Catalyzing the β‐Carboline Skeleton Construction in the Marinacarboline Biosynthetic Pathway

Abstract: Three genes, mcbABC, that drive the biosynthesis of marinacarbolines, have been elucidated through genome mining, gene inactivation, heterologous expression, feeding, and site-directed mutagenesis experiments. McbB is highlighted as a novel enzyme for the β-carboline core construction, which involves a Pictet-Spengler cyclization process and requiring E97 for biochemical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 27 publications
(20 reference statements)
0
57
0
3
Order By: Relevance
“…[72] McbB from Marinactinospora thermotolerans catalyzes the condensation between L-tryptophan ( 70 ) and oxaloacetaldehyde ( 71 ) to produce β-carboline ( 72 ). Although McbB displays a different protein fold from that of strictosidine synthase, site-directed mutagenesis studies of McbB identified Glu97 as the catalytic residue.…”
Section: Condensation Reactionsmentioning
confidence: 99%
“…[72] McbB from Marinactinospora thermotolerans catalyzes the condensation between L-tryptophan ( 70 ) and oxaloacetaldehyde ( 71 ) to produce β-carboline ( 72 ). Although McbB displays a different protein fold from that of strictosidine synthase, site-directed mutagenesis studies of McbB identified Glu97 as the catalytic residue.…”
Section: Condensation Reactionsmentioning
confidence: 99%
“…Particularly, there are nearly 64 identified β‐carboline alkaloids distributed across the eight plant families. Importantly, aromatic β‐carboline natural products (Figure ) eudistomin U, isoeudistomin, flazin, flazinamide, perlolyrine, harmane and harmine exhibit a wide range of biological activities such as antimalarial, antiviral, neuroprotection, anti‐HIV, anticancer, etc. Therefore, there has been considerable interest in the synthesis of β‐carbolines .…”
Section: Introductionmentioning
confidence: 99%
“…Pictet–Spenglerases have also been identified in bacterial secondary metabolism151617. The plant enzymes have a central role in engineered microbial systems for the production of alkaloids1819202122.…”
mentioning
confidence: 99%